Applied probability and stochastic processes - Beichelt, Frank, 1942- author (Boca Raton CRC Press, Taylor & Francis Group, 2016)
Beichelt offers numerous worked examples to represent stochastic processes in a user-friendly way. He includes a review of probability-theoretic topics and provides important proofs and theoretically challenging examples for the mathematically interested reader.
Part I: Probability Theory -- Part II: Stochastic Processes.
"A Chapman & Hall Book." Previous edition published as: Stochastic processes in science, engineering, and finance. 2006.
Includes bibliographical references (pages 549-552) and index.
Keywords: Stochastic processes; Probabilities